SPECIFICS OF CERAMIC COMPLEXES OF ISOLATED MOUND GROUPS № 1-5 OF THE PALASA-SYRT BURIAL GROUND OF IV-V CENTURIES - Magomedov, U A; Gmyra, L B (History, Archeology and Ethnography of the Caucasus, 2015)
The article deals with the specific character of the ceramic collection of five separate groups of graves (No. 1–5) of the southern section of the Palasa-Syrt burial mound of the 4th–5th cc., that were excavated within the period from 2009 to 2014. The authors characterize ceramic sets from each group of the graves, and on the basis of this characteristic they give a summary classification of the ceramic collection. The authors distinguish three groups of ceramic ware: table ceramics, kitchen ceramics and pottery of special purposes. The group of table ceramics includes five types of pitchers and their kinds, in the group of kitchen ceramics there are six types of pots, and a censer is considered to be the subject of special purpose. The authors conclude that the ceramic vessels from No. 1–5 mound groups of the Palasa-Syrt burial mound had no typological sameliness, considering both-the sets from separate groups of graves and the collection as a whole, although there are three types of pitchers that were most frequently used in the grave goods. The authors provide additional data on the ceramics–the distribution in the burial chamber, the number of vessels in the burial, the technology of their manufacture. The article presents the pictures of the ceramic vessels from each group of the graves and the typological complexes of ceramics of mound groups No. 1–5 as well.